The development of genus‐specific and species‐specific real‐time PCR assays for the authentication of Patagonian toothfish and Antarctic toothfish in commercial seafood products. (19th September 2021) - Yao, Lin; Qu, Meng; Jiang, Yanhua; Guo, Yingying; Li, Na; Li, Fengling; Tan, Zhijun; Wang, Lianzhu
Abstract: BACKGROUND: The substitution or mislabeling of toothfish is an issue of significant concern for seafood authorities; it also reduces the effectiveness of marine conservation and management programs for its over‐exploitation and illegal trafficking, boosting the need for identification methods. RESULTS: Two species‐specific real‐time polymerase chain reaction (PCR) assays for the identification of Patagonian toothfish ( Dissostichus eleginoides ) and Antarctic toothfish ( Dissostichus mawsoni ) and a genus‐specific real‐time PCR assay for Dissostichus spp. identification were developed based on fragments of the 16S rRNA and COI (cytochrome c oxidase subunit I) genes. These methods were confirmed to be rapid, simple, and sensitive (absolute sensitivity of 0.0002 ng μL −1 and relative sensitivity of 0.1 g kg −1 with good specificity). These methods can be applied to processed and commercial fish products. CONCLUSIONS: These approaches can be beneficial for protecting both consumers and producers from economic fraud and might also help protect toothfish from over‐exploitation as well as combat illegal, unreported, and unregulated (IUU) fisheries. © 2021 Society of Chemical Industry.